2020
DOI: 10.1002/adma.202002619
|View full text |Cite
|
Sign up to set email alerts
|

Crystal–Glass High‐Entropy Nanocomposites with Near Theoretical Compressive Strength and Large Deformability

Abstract: High‐entropy alloys (HEAs) and metallic glasses (MGs) are two material classes based on the massive mixing of multiple‐principal elements. HEAs are single or multiphase crystalline solid solutions with high ductility. MGs with amorphous structure have superior strength but usually poor ductility. Here, the stacking fault energy in the high‐entropy nanotwinned crystalline phase and the glass‐forming‐ability in the MG phase of the same material are controlled, realizing a novel nanocomposite with near theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 38 publications
(59 reference statements)
0
39
0
Order By: Relevance
“…If the size of the amorphous regions is smaller than 100 nm, shear banding events can be suppressed, leading to high strength and homogeneous plastic flow 35 . It has been demonstrated that crystal-glass nanocomposite alloys, with solid solution nanocrystals embedded in the amorphous matrix, reveal homogeneous plastic deformation, due to the confined plastic flow behavior of the amorphous phase 22 , 36 . Similarly, the amorphous-crystalline nanocomposite generated in the current study during wear benefits from this dual-phase structure, due to the resulting homogeneous plastic flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the size of the amorphous regions is smaller than 100 nm, shear banding events can be suppressed, leading to high strength and homogeneous plastic flow 35 . It has been demonstrated that crystal-glass nanocomposite alloys, with solid solution nanocrystals embedded in the amorphous matrix, reveal homogeneous plastic deformation, due to the confined plastic flow behavior of the amorphous phase 22 , 36 . Similarly, the amorphous-crystalline nanocomposite generated in the current study during wear benefits from this dual-phase structure, due to the resulting homogeneous plastic flow.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nanocomposites containing brittle crystalline phases usually reveal inhomogeneous plastic deformation due to shear banding 21 . If the brittle crystalline phase (such as crystalline oxide nanoparticles) in the nanocomposite is replaced by a ductile solid solution crystalline phase, homogeneous plastic deformation can be achieved 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al reported that the presence of nano-sized metallic glass shells surrounding grains in a nanocrystalline Al-Ni-Y alloy significantly improves the strength of the material, while also allowing for the achievement of plastic strains up to 76% in a microcompression experiment [28]. These authors also demonstrated the benefits that the inclusion of nanoscale amorphous metallic glass phases surrounding the grains of a multi-principal element alloy, demonstrating the achievement of near theoretical yield strength in a Cu-Co-Ni alloy surrounded by amorphous Fe-Si-B interfaces [29].…”
Section: Introductionmentioning
confidence: 88%
“…This trade-off is symbolic in nanocrystalline and amorphous alloys [13][14][15]. By contrast, the intro-duction of a nano-amorphous phase has high strength and ductility because of the high compressive strength exhibited by the amorphous size of less than 100 nm [11,12,16,17], and the shear banding phenomenon can be completely suppressed, thereby exhibiting flow behavior in deformation and thermal stability [18,19]. The currently reported nano-amorphouscrystalline dual-phase design has achieved strength-plasticity balance through partial crystallization by annealing amorphous elements [17], prenucleation by adding high-melting-point elements (e.g., tantalum or niobium) followed by rapid quenching [12,20], and embedding of nanocrystals into amorphous aggregates by magnetron sputtering [16].…”
Section: Introductionmentioning
confidence: 99%